A New Geometry of Multi-band MIMO Antenna for 5G and 6G Systems - Karrar Shakir Muttair; Oras Ahmed Shareef; Hazeem Baqir Taher; Faiz Arith (Journal of Techniques)
The demand for high-efficiency, small-sized ultrawide-band (UWB) antennas has risen due to the need for fast wireless communication systems. In this manuscript, we propose a novel geometry for a 4-port multi-in multi-out (MIMO) antenna with an L-shaped structure that solves the limitations of current designs in UWB applications. The dimensions and thickness of an antenna design are 18×18×1.5875 mm. It operates in multiple bands, such as Ku, K, and millimeter wave (mmWave) spectrum ranging from 17 to 100 GHz. This feature is ideal for small fifth-generation (5G) and sixth-generation (6G) wireless communication devices. We used two separate ground strips at the bottom to minimize interference in the MIMO element design and enhance antenna performance. The antenna performed exceptionally well in all measured parameters. The reflection coefficient (RC) was less than -10 dB, the mutual coupling (MC) coefficient reached -62.4 dB, and the radiation antenna efficiency ranged between 82% and 94%. It achieved the highest gain of 13 dBi at 87 GHz. In addition, the envelope correlation coefficient (ECC) is < 0.02, and the diversity gain (DG) ranges between 9.9 and 10 dB. This antenna surpasses all others in every parameter when compared to proposals by different researchers. This makes it a superior choice for modern wireless devices catering to 5G and 6G networks.